Energy management strategies and multi-objective optimization of a near-zero energy community energy supply system combined with hybrid energy storage. (August 2022) - Fan, Guangyao; Liu, Zhijian; Liu, Xuan; Shi, Yaxin; Wu, Di; Guo, Jiacheng; Zhang, Shicong; Yang, Xinyan; Zhang, Yulong
Highlights: A near-zero energy community energy system with hybrid energy storage is proposed. An energy management strategy combined with fuzzy logic method is schemed. A collaborative optimization model of system design and operation is built. The variation of different hydrogen vehicle charging modes on the system is analyzed. Abstract: A near-zero energy community energy system is an effective way to reduce fossil energy consumption and achieve a decarbonized and clean energy supply. However, the utilization proportion of renewable energy in the system is low, which is due to the lack of mature theoretical methods for energy management and optimization design. Therefore, this paper first proposes a near-zero energy community energy system that combines hydrogen storage, electricity storage, and heat storage. Second, considering the health state of energy storage, an energy management strategy is proposed that uses fuzzy logic to allocate electricity to hydrogen storage and electricity storage. On this basis, the novel energy system is applied to a diversified near-zero energy community that considers hydrogen vehicle loads. Subsequently, a multi-objective collaborative optimization method is used to design the system configuration and its related operation. The results indicate that the renewable energy proportion of the novel system is greater than 80%. The annual carbon emissions, annual total costs, and total grid interactions of the system are reduced by up to 155.3 t (8.2%), 41.6 k (2.3%), and 223.1 MWh (13.8%), respectively. This demonstrates the advantages of the new energy management strategy when compared with the fixed priority strategy.